2019
DOI: 10.1111/aje.12713
|View full text |Cite
|
Sign up to set email alerts
|

Species Distribution Modelling predicts habitat suitability and reduction of suitable habitat under future climatic scenario for Sclerophrys perreti: A critically endangered Nigerian endemic toad

Abstract: Sclerophrys perreti is a critically endangered Nigerian native frog currently imperilled by human activities. A better understanding of its potential distribution and habitat suitability will aid in conservation; however, such knowledge is limited for S. perreti. Herein, we used a species distribution model (SDM) approach with all known occurrence data (n = 22) from our field surveys and primary literature, and environmental variable predictors (19 bioclimatic variables, elevation and land cover) to elucidate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…One of the most important concerns of species distribution models is the assessment of areas in terms of coverage of suitable species habitats (Duan et al, 2016; Hu et al, 2017; Kafash et al, 2018; Nneji et al, 2019; Yousefi et al, 2017). In this study, the results of the assessment of the availability of suitable areas for two savannah species in West Africa in the future indicated a reduction of 5.04%, 6.08% and 6.51%, and 6.66% of suitable areas for H. nitidulus , respectively, under the two scenarios RCPs 4.5 and 8.5 by 2050 and 2070.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the most important concerns of species distribution models is the assessment of areas in terms of coverage of suitable species habitats (Duan et al, 2016; Hu et al, 2017; Kafash et al, 2018; Nneji et al, 2019; Yousefi et al, 2017). In this study, the results of the assessment of the availability of suitable areas for two savannah species in West Africa in the future indicated a reduction of 5.04%, 6.08% and 6.51%, and 6.66% of suitable areas for H. nitidulus , respectively, under the two scenarios RCPs 4.5 and 8.5 by 2050 and 2070.…”
Section: Discussionmentioning
confidence: 99%
“…In a study, focusing on identification of amphibian's conservation areas of south‐western Ghana, south‐eastern Côte d'Ivoire, northern Liberia, and the borders of Liberia with Guinea and Sierra Leone using 176 species and environmental variables (climatic factors and land cover parameters), Penner et al (2019) defined centres of high biodiversity of threatened, vulnerable, and endemic species by spatial modelling, but they did not take into account future projections on these species' distribution. More specifically, Nneji et al (2019) studied the predicted habitat distribution for Sclerophrys perreti (Schiøtz, 1963), an endemic toad in south‐western Nigeria, using future climate change models, and showed that temperature and precipitation were the predictors of habitat suitability with Precipitation Seasonality as the strongest predictor of habitat suitability. All these studies focused on threatened or vulnerable and endemic species in the forest and mountain regions, but few studies focused on savannah species, which are more widespread in the West African Sub‐Saharan region.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach evaluates changes in accuracy between a full model and the models where each environmental variable is omitted in turns (Qin et al, 2017; Schmitt et al, 2017; Urbani et al, 2017). Following past studies (Nneji et al, 2019; Senay et al, 2013), the SDM values were grouped into five classes as follows: not suitable = p < .4, poor = .4 < p < .5, moderate = .5 < p < .7, high = .7 < p < .9 and very high = p > .9.…”
Section: Methodsmentioning
confidence: 99%
“…These studies encompass tropical environments [ 14 , 15 ], circumpolar regions [ 11 , 16 ], and mountainous areas [ 17 ]. Some of these works are particularly significant as they analyze the climate impact on species with varying threat levels [ 9 , 18 ], especially endemic species [ 4 , 19 ].…”
Section: Introductionmentioning
confidence: 99%